Controllable heat release type lightweight concrete and preparation method thereof

By using the composite foaming agent of hydrogen peroxide and nitrogen methalotate, and the pre -frozen water frozen treatment of high water absorption resin, the problem of the heat accumulation effect during the preparation of ultra -light concrete preparation, significantly improved the structural stability and of the material's structure stability and Mechanical performance.

CN119330655AActive Publication Date: 2025-01-21CHINA BUILDING MATERIALS ACADEMY CO LTD

Patent Information

Application Number
CN202411292709.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-21
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

In the preparation process of existing ultra-light concrete, bubble breakage, hole wall defects and heat accumulation effects are prone to occur, affecting the quality and performance of the material.

Method used

The mixture of hydrogen peroxide and nitrogen hydramium ethyl acetate is used as a composite foaming agent. By adjusting its ratio, the heat released by hydrogen peroxide is used to stimulate the low -decomposition heat foam of the alcohol of nitrogen. Pre -water -filled water frozen treatment of high water absorption resin relieves local high temperature.

Benefits of technology

Effectively avoid the defects of bubbles and hole wall, significantly improve the structural stability of the bubbles and the mechanical properties of concrete, and improve its application performance in the traffic blocking system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045081050000051
    Figure BDA0005045081050000051
  • Figure BDA0005045081050000071
    Figure BDA0005045081050000071
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses controllable heat release type lightweight concrete and a preparation method thereof. The controllable heat release type lightweight concrete provided by the invention is prepared from the following components in parts by weight: 250 to 320 parts of cement, 2.4 to 3.7 parts of foam stabilizer, 2 to 2.6 parts of composite foaming agent, 5 to 10 parts of super absorbent resin, 1 to 4 parts of accelerator, 3 to 9 parts of water reducing agent, 0.5 to 2 parts of fiber and 130 to 180 parts of water, the composite foaming agent is prepared from hydrogen peroxide and ethyl azidoformate in a weight ratio of 1: (0.15-0.35); the invention further provides a preparation method of the controllable heat release type lightweight concrete. The controllable heat release type lightweight concrete provided by the invention is stable in bubble structure and small in temperature change amplitude in the foaming process, foam breaking, hole wall defects and a heat accumulation effect are avoided, and the obtained lightweight concrete is good in crumple performance and excellent in mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete, and in particular to a controllable heat-release lightweight concrete and a preparation method thereof. Background Art

[0002] Ultra-lightweight concrete is a new type of building material with low density, high strength and good shrinkage energy absorption characteristics. It is widely used in traffic engineering fields such as highway escape lanes and airport runway end arresting systems. Compared with traditional concrete, ultra-lightweight concrete reduces the density of concrete materials by introducing bubbles, thereby reducing the structural deadweight of concrete and improving the performance and construction efficiency of concrete.

[0003] At present, the foaming agent used in the preparation of ultra-lightweight concrete is mainly hydrogen peroxide, which catalytically decomposes to produce oxygen and form a uniform bubble structure. However, during the decomposition process of the above-mentioned foaming agent, there will be a problem of excessive temperature, which will cause the lightweight concrete to be prone to bubble breaking, pore wall defects and heat accumulation effects, which seriously affects the quality and performance of ultra-lightweight concrete and limits its wide application in traffic blocking projects. Summary of the invention

[0004] In order to solve the problems of bubble breaking, pore wall defects and heat accumulation effect that are prone to occur in the existing ultra-lightweight concrete preparation process, the present application provides a controllable heat release lightweight concrete.

[0005] In a first aspect, the present application provides a controllable heat release type lightweight concrete, which adopts the following technical solution: A controllable heat release type lightweight concrete comprises the following components in parts by weight: 250-320 parts of cement, 2.4-3.7 parts of foam stabilizer, 2-2.6 parts of composite foaming agent, 5-10 parts of highly absorbent resin, 1-4 parts of accelerating setting agent, 3-9 parts of water reducing agent, 0.5-2 parts of fiber and 130-180 parts of water; The composite foaming agent is hydrogen peroxide and ethyl azide formate in a weight ratio of 1: (0.15-0.35).

[0006] The present application provides a controlled heat release type lightweight concrete, which uses a mixture of hydrogen peroxide and ethyl azide as a foaming agent. By adjusting the ratio of hydrogen peroxide to ethyl azide, the heat released by hydrogen peroxide is effectively used to stimulate the decomposition and foaming of ethyl azide with low decomposition heat. On the one hand, it avoids the defect of hydrogen peroxide as a single foaming agent, which has a huge heat release and causes bubble breakage or pore wall defects. On the other hand, the foaming effect of the two components is significant and the structural stability of the bubbles is better. The bubbles in the controlled heat release type lightweight concrete prepared by the above-mentioned composite foaming agent in the present application are of appropriate size, good uniformity, and good mechanical properties. It is used in arresting systems such as airport runways, and can give full play to its collapse energy absorption characteristics, thereby efficiently arresting accident vehicles such as crashed aircraft.

[0007] In some embodiments, the weight ratio of hydrogen peroxide to ethyl azide can be 1:(0.15-0.2), 1:(0.15-0.25), 1:(0.15-0.3), 1:(0.15-0.35), 1:(0.2-0.25), 1:(0.2-0.3), 1:(0.2-0.35), 1:(0.25-0.3), 1:(0.25-0.35) or 1:(0.3-0.35).

[0008] In a specific embodiment, the weight ratio of the hydrogen peroxide to ethyl azide formate can also be 1:0.15, 1:0.2, 1:0.25, 1:0.3 or 1:0.35.

[0009] Optionally, the weight ratio of the hydrogen peroxide to ethyl azide formate is 1:(0.2-0.3).

[0010] Optionally, the foaming agent is prepared by mixing hydrogen peroxide and ethyl azide formate, and stirring the mixture at a rotation speed of 300-500 rpm for 90-150 seconds to obtain a composite foaming agent.

[0011] Optionally, the super absorbent resin is acrylamide-sodium acrylate copolymer, with a particle size of 80 to 700 μm and a bulk density of 0.6 to 0.9 g / cm 3 , water retention rate ≥85%.

[0012] Optionally, the super absorbent resin needs to be pre-saturated with water and frozen before use.

[0013] In the present application, by pre-saturating the super absorbent resin with water and freezing it, part of the water can be frozen and sealed. During the preparation and curing process of concrete, the frozen and sealed water can absorb the heat in the concrete, especially the heat generated by the decomposition of hydrogen peroxide, through melting, thereby playing a cooling role; in addition, during the melting process of the frozen water, not only can the local high temperature caused by the cement hydration reaction and the decomposition of the foaming agent be effectively alleviated, but also the gradually released water can provide a long-lasting internal curing effect for the concrete, promote the uniform hydration of cement particles, and thus improve the densification of the microstructure of the concrete and the macro-collapse performance.

[0014] Optionally, the foam stabilizer is selected from one or more of methyl cellulose ether, hydroxyethyl cellulose ether, hydroxyethyl methyl cellulose ether, hydroxypropyl methyl cellulose ether, stearate series foam stabilizers, styrene-butadiene emulsion and ethylene-vinyl acetate emulsion.

[0015] Optionally, the foam stabilizer is a mixture of hydroxyethyl cellulose ether and calcium stearate in a weight ratio of 1:(3-6).

[0016] In some embodiments, the weight ratio of the hydroxyethyl cellulose ether to calcium stearate may be 1:(3-4), 1:(3-5), 1:(3-6), 1:(4-5), 1:(4-6) or 1:(5-6).

[0017] In a specific embodiment, the weight ratio of the hydroxyethyl cellulose ether to calcium stearate can also be 1:3, 1:4, 1:5, or 1:6.

[0018] Optionally, the water reducer is selected from one or more of a polycarboxylic acid water reducer, a naphthalene water reducer, an anthracene water reducer, a lignin sulfonate water reducer, an aminosulfonate water reducer, an aliphatic water reducer and a melamine water reducer; The accelerating setting agent is selected from one or more of alumina clinker accelerating setting agents, water glass accelerating setting agents, aluminate accelerating setting agents and aluminum sulfate accelerating setting agents; The water reducer is selected from one or more of polycarboxylic acid water reducer, naphthalene water reducer, anthracene water reducer, lignin sulfonate water reducer, aminosulfonate water reducer, aliphatic water reducer and melamine water reducer; The fiber is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

[0019] Optionally, the cement is low-heat silicate cement with low hydration heat, the clinker dicalcium silicate content is ≥40%, or the iron phase content is ≥15%, and specifically, one of high belite silicate cement and road silicate cement can be selected.

[0020] The present application selects high-belite silicate cement or road silicate cement with low hydration heat characteristics to overcome the problem of high heat caused by the cementitious components of traditional ultra-light concrete materials, and at the same time solves the problem of compatibility between existing silicate cement and auxiliary cementitious materials.

[0021] In a second aspect, the present application provides a method for preparing the above-mentioned controlled heat release lightweight concrete.

[0022] A method for preparing a controllable heat release lightweight concrete comprises the following steps: Mix cement, foam stabilizer and fiber evenly to obtain dry mixed material; Disperse the water reducer in half of the water, mix with the dry mixed material, and stir evenly; then add the accelerating setting agent, stir evenly, and obtain slurry; The foaming agent is mixed with the remaining water, stirred at a rotation speed of 1000-3000 rpm for 40-60 seconds, and then the frozen highly absorbent resin and the foaming agent are added to the slurry together, stirred at a rotation speed of 500-600 rpm for 60-180 seconds to obtain a controllable heat release lightweight concrete.

[0023] Optionally, the frozen super absorbent resin is prepared by immersing the super absorbent resin in water for 5 to 60 minutes, and then freezing it at -(15 to 25)°C for 1 to 6 hours to obtain the frozen super absorbent resin.

[0024] In summary, this application has the following beneficial effects: 1. The present application uses a mixture of hydrogen peroxide and ethyl azide as a foaming agent. By adjusting the ratio of hydrogen peroxide to ethyl azide to within the range of 1: (0.15-0.35), the defects of hydrogen peroxide as a single foaming agent, such as the huge heat release causing bubble breakage or pore wall defects, are effectively avoided. The foaming effect of the concrete is significant, the structural stability of the bubbles is good, and the crushability of the obtained concrete is ≥0.6 and the semi-collapse energy is ≥110-116J.

[0025] 2. The present application can alleviate the local high temperature in the process of concrete preparation by pre-saturating and freezing the highly absorbent resin, and provide a lasting internal curing effect for the concrete, effectively promoting the uniform hydration of cement particles, thereby improving the densification of the microstructure of the concrete and the macro-shrinkage performance.

[0026] 3. The present application further selects a mixture of hydroxyethyl cellulose ether and calcium stearate in a weight ratio of 1:(3-6) as a foam stabilizer, and the obtained concrete has better performance. DETAILED DESCRIPTION

[0027] The present application provides a controlled heat release type lightweight concrete, comprising the following components in parts by weight: 250-320 parts of cement, 2.4-3.7 parts of foam stabilizer, 2-2.6 parts of composite foaming agent, 5-10 parts of super absorbent resin, 1-4 parts of accelerator, 3-9 parts of water reducer, 0.5-2 parts of fiber and 130-180 parts of water; the composite foaming agent is hydrogen peroxide and ethyl azide in a weight ratio of 1: (0.15-0.35); further, the weight ratio of hydrogen peroxide to ethyl azide is 1: (0.2-0.3). The super absorbent resin is an acrylamide-sodium acrylate copolymer, with a particle size of 80-700 μm and a bulk density of 0.6-0.9 g / cm 3 , water retention rate ≥85%.

[0028] The foam stabilizer is selected from one or more of methyl cellulose ether, hydroxyethyl cellulose ether, hydroxyethyl methyl cellulose ether, hydroxypropyl methyl cellulose ether, stearate series foam stabilizers, styrene-butadiene emulsion and ethylene-vinyl acetate emulsion. Further, the foam stabilizer is a mixture of hydroxyethyl cellulose ether and calcium stearate in a weight ratio of 1:(3-6).

[0029] The water reducer is selected from one or more of polycarboxylic acid water reducers, naphthalene water reducers, anthracene water reducers, lignin sulfonate water reducers, aminosulfonate water reducers, aliphatic water reducers and melamine water reducers; the accelerator is selected from one or more of alumina clinker accelerators, water glass accelerators, aluminate accelerators and aluminum sulfate accelerators; the water reducer is selected from one or more of polycarboxylic acid water reducers, naphthalene water reducers, anthracene water reducers, lignin sulfonate water reducers, aminosulfonate water reducers, aliphatic water reducers and melamine water reducers; the fiber is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

[0030] The present application also provides a method for preparing the above-mentioned controllable heat release type lightweight concrete, comprising the following steps: (1) Weighing each component according to weight; immersing the super absorbent resin in water for 5 to 60 minutes, and then freezing it at -(15 to 25)°C for 1 to 6 hours to obtain a frozen super absorbent resin.

[0031] (2) Put cement, foam stabilizer and fiber into a mixer and mix and stir for 60-120 seconds to obtain a dry mixed material; (3) Disperse the water reducer in half of the water and inject it into the dry mixed material, mix and stir evenly; then add the accelerator and continue stirring for 60-120 seconds to obtain a slurry; (4) Mix the foaming agent with the remaining water, stir at a speed of 1000-3000 rpm for 40-60 seconds, then add the frozen super absorbent resin and the foaming agent into the slurry, stir at a speed of 500-600 rpm for 60-180 seconds, and obtain a controlled heat release lightweight concrete.

[0032] In the examples of this application, cement is selected from high Belite 42.5 low-heat silicate cement, purchased from Jiahua Special Cement Co., Ltd.; hydroxyethyl cellulose ether is purchased from Feicheng Yutian Chemical Co., Ltd.; calcium stearate foam stabilizer is purchased from Jingjiang Guangsheng Rubber and Plastic Material Factory; super absorbent resin is acrylamide-sodium acrylate copolymer, purchased from Shandong Huadi New Materials Co., Ltd.; water reducer is polycarboxylic acid water reducer, model PC-311; accelerator model is ZY-98; fiber is polypropylene fiber, purchased from Shandong Honggu New Materials. The raw materials, reagents, solvents, etc. used in this application can all be obtained commercially.

[0033] The present application is further described in detail below in combination with preparation examples, embodiments and performance testing experiments.

[0034] Preparation Example 1-5 Preparation Examples 1-5 each provide a composite foaming agent.

[0035] The difference between the above preparation examples is that the weight ratio of hydrogen peroxide to ethyl azide formate is as shown in Table 1 below.

[0036] The preparation method of the composite foaming agent provided in Preparation Example 1-5 is: mixing hydrogen peroxide and ethyl azide formate, stirring at a rotation speed of 400 rpm for 120 seconds, to obtain a composite foaming agent.

[0037] Table 1 Weight ratio of hydrogen peroxide to ethyl azide in the composite foaming agent provided in Preparation Examples 1-5 Comparative Preparation Example 1 Comparative Preparation Example 1 provides a composite foaming agent.

[0038] The difference between the comparative preparation example and preparation example 3 is that the added amount of ethyl azide formate is 0.5 kg, that is, the weight ratio of hydrogen peroxide to ethyl azide formate is 1:0.5.

[0039] Examples 1-5 Examples 1-5 each provide a controlled heat release type lightweight concrete.

[0040] The difference between the above embodiments is that the composite foaming agent in the controlled heat release type lightweight concrete is derived from Preparation Examples 1-5 respectively.

[0041] The method for preparing the controlled heat release lightweight concrete provided in Examples 1-5 comprises the following steps: (1) Weigh the following components by weight: 28 kg of cement, 0.3 kg of hydroxyethyl cellulose ether, 0.23 kg of composite foaming agent, 0.8 kg of super absorbent resin, 0.2 kg of accelerator, 0.6 kg of water reducer, 0.1 kg of fiber and 15 kg of water; The super absorbent resin is immersed in water for 30 minutes, and then frozen at -20°C for 3 hours to obtain the frozen super absorbent resin.

[0042] (2) Put cement, foam stabilizer and fiber into a mixer and mix and stir for 90 seconds to obtain a dry mixed material; (3) Disperse the water reducer in 7.5 kg of water and inject it into the dry mixed material, mix and stir evenly; then add the accelerator and continue stirring for 90 seconds to obtain a slurry; (4) The foaming agent was mixed with the remaining 7.5 kg of water, and stirred at a rotation speed of 2000 rpm for 50 seconds. Then, the frozen superabsorbent resin and the foaming agent were added to the slurry, and stirred at a rotation speed of 550 rpm for 120 seconds to obtain a controlled heat release lightweight concrete.

[0043] Example 6 Example 6 provides a controlled heat release lightweight concrete.

[0044] The difference between the above embodiment and embodiment 3 is that the highly absorbent resin in the controlled heat release type lightweight concrete is not subjected to pre-saturated water freezing treatment but is directly added to the concrete.

[0045] Embodiment 7-13 Examples 7-13 each provide a controlled heat release type lightweight concrete.

[0046] The difference between the above embodiment and embodiment 3 is that the type and proportion of the foam stabilizer in the controlled heat release lightweight concrete are specifically shown in Table 2 below.

[0047] Table 2 Types and proportions of foam stabilizers in Preparation Examples 3 and 7-13 Preparation Example Foam stabilizer 3 Hydroxyethyl cellulose ether 7 Calcium stearate 8 Hydroxyethyl cellulose ether and calcium stearate in a weight ratio of 1:3 9 Hydroxyethyl cellulose ether and calcium stearate in a weight ratio of 1:4 10 Hydroxyethyl cellulose ether and calcium stearate in a weight ratio of 1:5 11 Hydroxyethyl cellulose ether and calcium stearate in a weight ratio of 1:6 12 Hydroxyethyl cellulose ether and methyl cellulose ether in a weight ratio of 1:4 13 Methyl cellulose ether and calcium stearate in a weight ratio of 1:4 Comparative Example 1 Comparative Example 1 provides a controlled heat release type lightweight concrete.

[0048] The difference between the comparative example and Example 3 is that the composite foaming agent in the controlled heat release type lightweight concrete is replaced by hydrogen peroxide.

[0049] Comparative Example 2 Comparative Example 2 provides a controlled heat release lightweight concrete.

[0050] The difference between the comparative example and Example 3 is that the composite foaming agent in the controlled heat release type lightweight concrete is replaced by ethyl azide formate.

[0051] Performance testing The performance of the controlled heat release lightweight concrete provided in Examples 1-13 and Comparative Examples 1-2 was tested, and the results are shown in Table 3 below.

[0052] (1) Pore structure: Take any side of a 100 mm × 100 mm × 100 mm specimen and cut it vertically downward along the line connecting the midpoints of two non-adjacent sides of the specimen to obtain a 100 mm × 100 mm section; paint the section black with ink, and fill the open pores of the section with white calcium carbonate powder; scan the section using a flatbed scanning method; then use Photoshops to perform black and white binary processing, and use Image-Pro plus image software to analyze the pore size and distribution of ultra-lightweight concrete.

[0053] (2) Shrinkage (mechanical properties): The ratio of the concrete crush depth to its height. The greater the shrinkage, the greater the crush depth of the material and the worse the mechanical properties of the material.

[0054] (3) Half-collapse energy: the total energy absorbed by concrete when the degree of collapse reaches 0.5. The larger the half-collapse energy, the better the collapse energy absorption property of the material and the higher the safety factor of the material.

[0055] Table 3 Performance test results of lightweight concrete obtained from Examples 1-13 and Comparative Examples 1-2 According to the test results in Table 3, the pore size distribution of the controlled heat release lightweight concrete obtained in Examples 1-13 of the present application is mainly concentrated in the range of 1.5 to 2.0 mm, the shrinkage degree of the lightweight concrete is 0.61-0.85, and the semi-collapse energy is 110.4-120.5 J; while the pore size distribution of the lightweight concrete obtained in Comparative Example 1 is mainly concentrated in the range of 1.5 to 3.0 mm, the pore size distribution is relatively wide, and the shrinkage degree of the obtained lightweight concrete is 0.92, and the semi-collapse energy is 98.4 J; the pore size distribution of the lightweight concrete obtained in Comparative Example 2 is mainly concentrated in the range of 1.0 to 3.0 mm, the pore size distribution is relatively wide, and the shrinkage degree of the obtained lightweight concrete is 0.90, and the semi-collapse energy is 96.45 J. Therefore, it is shown that the bubbles in the controlled heat release lightweight concrete provided in the present application are of appropriate size, good uniformity, and excellent mechanical properties. When used in arresting systems such as airport runways, it can give full play to its collapse energy absorption characteristics and achieve efficient arrestment of accident vehicles such as crashed aircraft.

[0056] The test results of Examples 1-5 show that the proportion of pores of 1.5-2.0 mm in the lightweight concrete obtained in Examples 2-4 is 57.31-65.84%, the shrinkage of the lightweight concrete is 0.73-0.78, and the half-collapse energy is 114.3-116.5 J; while the proportion of pores of 1.5-2.0 mm in the lightweight concrete obtained in Examples 1 and 5 is 46.77-49.36%, the shrinkage of the lightweight concrete is 0.80-0.81, and the half-collapse energy is 110.4-112.6 J, indicating that the present application further controls the weight ratio of hydrogen peroxide to ethyl azide in the composite foaming agent within the range of 1: (0.2-0.3), and the obtained lightweight concrete has better bubble uniformity and stability, and better shrinkage performance The test results of Example 3 and Example 6 show that the shrinkage performance of the lightweight concrete obtained in Example 3 is significantly better than that of the lightweight concrete obtained in Example 6, indicating that pre-saturated freezing treatment of the super absorbent resin can improve the hydration effect of cement in concrete, thereby improving the shrinkage performance of the concrete.

[0057] The test results of Examples 3 and 7-13 show that in Examples 3 and 7, hydroxyethyl cellulose ether or calcium stearate is used as a foam stabilizer, and the proportion of pores of 1.5 to 2.0 mm in the obtained lightweight concrete is 59.72-65.84%, the shrinkage degree of the lightweight concrete is 0.73-0.78, and the half-collapse energy is 113.2-116.5 J; in Examples 8-11, a mixture of hydroxyethyl cellulose ether and calcium stearate is used as a foam stabilizer, and the proportion of pores of 1.5 to 2.0 mm in the obtained lightweight concrete is 59.72-65.84%, the shrinkage degree of the lightweight concrete is 0.73-0.78, and the half-collapse energy is 113.2-116.5 J. The pore ratio is 68.73-72.45%, the shrinkage of the lightweight concrete is 0.61-0.65, and the half-collapse energy is 117.2-120.5 J. Examples 12-13 use a mixture of hydroxyethyl cellulose ether and methyl cellulose ether or a mixture of methyl cellulose ether and calcium stearate, and the pore ratio of 1.5-2.0 mm in the obtained lightweight concrete is 58.97-66.35%, the shrinkage of the lightweight concrete is 0.69-0.72, and the half-collapse energy is 116.8-117.1 J. Therefore, it is explained that the present application uses a mixture of hydroxyethyl cellulose ether and calcium stearate as a foam stabilizer, and the obtained lightweight concrete has better shrinkage performance.

[0058] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A controlled heat release lightweight concrete, characterized in that: The invention comprises the following components in parts by weight: 250-320 parts of cement, 2.4-3.7 parts of foam stabilizer, 2-2.6 parts of composite foaming agent, 5-10 parts of highly absorbent resin, 1-4 parts of accelerating setting agent, 3-9 parts of water reducing agent, 0.5-2 parts of fiber and 130-180 parts of water; The composite foaming agent is hydrogen peroxide and ethyl azide formate in a weight ratio of 1: (0.15-0.35).

2. The controlled heat release lightweight concrete according to claim 1, characterized in that: The weight ratio of the hydrogen peroxide to ethyl azide formate is 1:(0.2-0.3).

3. The controlled heat release lightweight concrete according to claim 1, characterized in that: The preparation method of the foaming agent is as follows: hydrogen peroxide and ethyl azide are mixed, and the mixture is stirred at a rotation speed of 300-500 rpm for 90-150 seconds to obtain a composite foaming agent.

4. The controlled heat release lightweight concrete according to claim 1, characterized in that: The super absorbent resin is acrylamide-sodium acrylate copolymer with a particle size of 80-700 μm and a bulk density of 0.6-0.9 g / cm 3 , water retention rate ≥85%.

5. The controlled heat release lightweight concrete according to claim 1, characterized in that: The super absorbent resin needs to be pre-saturated with water and frozen before use.

6. The controlled heat release lightweight concrete according to claim 1, characterized in that: The foam stabilizer is selected from one or more of methyl cellulose ether, hydroxyethyl cellulose ether, hydroxyethyl methyl cellulose ether, hydroxypropyl methyl cellulose ether, stearate series foam stabilizers, styrene-butadiene emulsion and ethylene-vinyl acetate emulsion.

7. The controlled heat release lightweight concrete according to claim 1, characterized in that: The foam stabilizer is a mixture of hydroxyethyl cellulose ether and calcium stearate in a weight ratio of 1:(3-6).

8. The controlled heat release lightweight concrete according to claim 1, characterized in that: The water reducer is selected from one or more of polycarboxylic acid water reducer, naphthalene water reducer, anthracene water reducer, lignin sulfonate water reducer, aminosulfonate water reducer, aliphatic water reducer and melamine water reducer; The accelerating setting agent is selected from one or more of alumina clinker accelerating setting agents, water glass accelerating setting agents, aluminate accelerating setting agents and aluminum sulfate accelerating setting agents; The water reducer is selected from one or more of polycarboxylic acid water reducer, naphthalene water reducer, anthracene water reducer, lignin sulfonate water reducer, aminosulfonate water reducer, aliphatic water reducer and melamine water reducer; The fiber is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

9. The method for preparing controlled heat release lightweight concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mix cement, foam stabilizer and fiber evenly to obtain dry mixed material; Disperse the water reducer in half of the water, mix with the dry mixed material, and stir evenly; then add the accelerating setting agent, stir evenly, and obtain slurry; The foaming agent is mixed with the remaining water, stirred at a rotation speed of 1000-3000 rpm for 40-60 seconds, and then the frozen highly absorbent resin and the foaming agent are added to the slurry together, stirred at a rotation speed of 500-600 rpm for 60-180 seconds to obtain a controllable heat release lightweight concrete.

10. The method for preparing controlled heat release lightweight concrete according to claim 9, characterized in that: The method for preparing the frozen super absorbent resin is as follows: immersing the super absorbent resin in water for 5 to 60 minutes, and then freezing it at -(15 to 25)°C for 1 to 6 hours to obtain the frozen super absorbent resin.

Citation Information

Patent Citations

  • Non-autoclaved lightweight thermal insulation particle aerated concrete block and preparation method thereof

    CN111807807A

  • Preparation method of lightweight high-strength anti-crack foam concrete and lightweight batten

    CN117602962A

  • Process for modifying hydrocarbon polymers with lower aliphatic monoazidoformates

    US3211713A

Cited By

  • Preparation method of biomass air entraining agent blended concrete

    CN119977485A